The Impact on Workers' Compensation Insurance Markets of Allowing the Terrorism Risk Insurance Act to Expire - Dworsky, Michael (RAND Corporation, 2014)
Congress enacted the Terrorism Risk Insurance Act (TRIA) in 2002, in response to terrorism insurance becoming unavailable or extremely costly in the wake of the 9/11 attacks. TRIA is set to expire at the end of 2014, and Congress is considering the appropriate government role in terrorism insurance markets. This policy brief examines how markets for workers' compensation insurance would be affected if TRIA were to expire.